How the 2008 financial crisis affected the Spanish economy due to household income - Miguel Á. Martínez-García; Ángeles Cámara (National Accounting Review)
Economic crises do not affect all households in the same way; therefore, it is crucial to analyze the differences in their impact based on household income. The last economic crisis, the financial crisis of 2008, lasted until 2013 in Spain; however, economic recovery was not considered to have been effectively achieved until 2016, when economic performance exceeded the pre-crisis level. Economic recovery was not reflected in households in the same way because of household income inequalities. This study identified the different effects of an economic crisis on households and economic sectors through a multisectoral model by analyzing the consumption behaviors of households according to monthly income after the crisis. A simulation was carried out based on consumption data for 2015, which identified the production sectors that suffered the greatest losses because of a crisis-induced decrease in household consumption spending. The results reveal that the decrease in low-income household consumption mainly affected accommodation and food services, manufactured products, wholesale and retail trade services, and activity generated by households as employers of domestic workers.